Reading: An overview prior to reading comprehension - Peñafiel Arcos, Edison Boanerges (SATHIRI, 2018)
Reading comprehension is defined as the level of understanding of a text/message. This understanding comes from the interaction between the words that are written and how they trigger knowledge outside the text/message. Another important component of reading comprehension is the activation of prior knowledge or making connections while reading. So, Readers must be able to draw from their experiences to apply what they are reading. If a student is not able to activate the schema necessary for a specific piece of text, his or her comprehension will be either distorted or greatly hindered.  For decades, a great amount of studies have been done to investigate the influences of reading strategies on readers"™ comprehension. It has no longer been considered as a static and passive process in decoding words and recoding meanings of individual words or phrases. Instead, reading comprehension has been deemed as an active, dynamic, and growing process of searching for interrelationships in a text. In this context, this research presents those fundamentals that readers bring to the text, the factors that affect reading, as well as the reading phases and their supportive strategies.